2021
DOI: 10.1051/0004-6361/202141462
|View full text |Cite
|
Sign up to set email alerts
|

Solar inertial modes: Observations, identification, and diagnostic promise

Abstract: The oscillations of a slowly rotating star have long been classified into spheroidal and toroidal modes. The spheroidal modes include the well-known 5-min acoustic modes used in helioseismology. Here we report observations of the Sun's toroidal modes, for which the restoring force is the Coriolis force and whose periods are on the order of the solar rotation period. By comparing the observations with the normal modes of a differentially rotating spherical shell, we are able to identify many of the observed mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
121
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(142 citation statements)
references
References 33 publications
19
121
2
Order By: Relevance
“…The highest amplitude mode (∼ 10 -20 m s −1 above 50 • latitude) is the m = 1 mode with north-south antisymmetric longitudinal velocity v φ with respect to the equator. This m = 1 mode was identified by Gizon et al (2021) using linear calculations in two-dimensional model, which are further discussed in the present paper and Fournier et al (2022). It corresponds to the spiral-like velocity feature reported at high latitudes by Hathaway et al (2013), although it was there reported as giantcell convection.…”
Section: Solar Inertial Modessupporting
confidence: 64%
See 3 more Smart Citations
“…The highest amplitude mode (∼ 10 -20 m s −1 above 50 • latitude) is the m = 1 mode with north-south antisymmetric longitudinal velocity v φ with respect to the equator. This m = 1 mode was identified by Gizon et al (2021) using linear calculations in two-dimensional model, which are further discussed in the present paper and Fournier et al (2022). It corresponds to the spiral-like velocity feature reported at high latitudes by Hathaway et al (2013), although it was there reported as giantcell convection.…”
Section: Solar Inertial Modessupporting
confidence: 64%
“…Fournier et al (2022) extended this model to a spherical geometry using a realistic differential rotation model and found that some Rossby modes can be unstable for m ≤ 3. Gizon et al (2021) also report a family of modes at midlatitudes that are localized near their critical latitudes. Several tens of critical-latitude modes have been identified in the range m ≤ 10.…”
Section: Solar Inertial Modesmentioning
confidence: 90%
See 2 more Smart Citations
“…Notable local helioseismic results include imaging of the meridional flow (Giles et al 1997;Gizon et al 2020) through time-distance helioseismology (Duvall et al 1993), and farside imaging of active regions (Braun & Lindsey 2001) and their near side emergence (Birch et al 2016), through helioseismic holography (Lindsey & Braun 2000). The recent discovery of various inertial waves (Gizon et al 2021), including the equatorial Rossby wave (Löptien et al 2018), has been achieved through local helioseismic ring-diagram analysis (Hill 1988) and the non-helioseismic local correlation tracking (LCT, November & Simon 1988) of granulation.…”
Section: Introductionmentioning
confidence: 99%